Akulturasi Agama dan Budaya Lamaran Ngunggah- Ngungahi dalam Adat Kawin Colong di Banyuwangi - Qurrotul Ainiyah (SAMAWA, 2025)
Ngunggah-ngunggahi is a proposal tradition in the Osing Banyuwangi tribe called colong. The purpose of this study is to find out information about the thoughts of the Osing people about the relationship between religion and the culture of ngungggah-ngunggahi proposals. So that the customs carried out will be in line with Islamic teachings. With an ethnographic approach, this study produces; First, ngunggah-ngunggahi proposals are part of the colong marriage custom. This custom is carried out because the couple wants to get married, but does not get the blessing of the parents of the prospective bride. By carrying out the ngunggahi-ngunggahi custom, the Osing people have carried out a "symbology process", because the Osing people consider Wong Osing who carry out the colongan ritual to be brave and responsible men because they are able to fight for their love to the level of marriage. Second, the acculturation of religion and culture in the ngunggah ngunggahi custom is formed from local wisdom combined with Islamic values. The position of Islamic values ​​as a high tradition is used as a basis for the ngunggah-ngunggahi tradition (low tradition). Islamic values ​​are seen from the restrictions on the social interaction of prospective brides and grooms in colong activities adjusted to Islamic teachings, and include readings of the holy verses of the Qur'an, prayers and prayers taught by scholars in the following ritual processes. Thus, the acculturation of religion and culture in the ngunggah-ngunggahi tradition is formed in a cultural space that can be accepted by all Osing people in Banyuwangi